Smells like debauchery: The chemical composition of semen-like, sweat-like and faintly foetid floral odours in Xysmalobium (Apocynaceae: Asclepiadoideae). (June 2016) - Shuttleworth, Adam
Abstract: Floral volatiles play an important role in plant communication with both pollinators and antagonists, but remain poorly explored for many plant groups. Asclepiads (Apocynaceae: Asclepiadoideae subtribe Asclepiadinae) represent a diverse group in South African grasslands, but the scents of most species remain unexplored and few genera are sufficiently sampled to allow comparisons between congeners. I used dynamic headspace extraction methods and coupled gas chromatography-mass spectrometry (GC–MS) to examine the scent chemistry of three unusually scented asclepiads in the genus Xysmalobium and then combined these data with previously published data to explore inter- and intraspecific variation in the genus. A total of 74 compounds (33–44 per species) from various compound classes were detected in the species examined here. The sweet but faintly foetid scent of Xysmalobium asperum was dominated by epoxy oxoisophorone in combination with various other terpenoids and aromatics, and small amounts of p -cresol. The sweat-like scent of Xysmalobium tysonianum was dominated by a few aromatics in combination with isovaleric acid and several aliphatic compounds normally associated with microbial degradation or fermentation. The semen-like scent of Xysmalobium parviflorum flowers examined here contained large relative amounts of 1-pyrroline, and comparison with previously published data for dung-scented flowers from a different population revealed clear divergence in the relative amounts of this compound and p -cresol. I also detected 25 compounds that were not shared between the two X. parviflorum populations. Comparison of scent data for eight Xysmalobium species revealed very distinct chemical profiles with limited overlap between species. These results are discussed in relation to the possible roles of these volatiles as pollinator attractants and the evolution of floral scents within the genus. Highlights: Semen scented Xysmalobium parviflorum flowers produce large amounts of 1-pyrroline. Sweaty scented X. tysonianum produce isovaleric acid and several foetid aliphatics. X. asperum scent dominated by epoxy oxoisophorone with other terpenoids and aromatics. Clear variation in scent chemistry between populations of X. parviflorum . Minimal overlap between total scent profiles of 8 Xysmalobium species.